Immigrati e cittadinanza. Una questione di accoglienza? - Gozzo, Simona (SocietàMutamentoPolitica, 2016)
This study analyzes the relationship between theoretical models of European integration and inclusion or exclusion of immigrants. The main hypothesis is that relations are key in understanding and explaining differences between material and formal integration, including propensity towards social involvement and focusing on the acquisition of citizenship. Data collected in an Italian local context are applied for an in-depth analysis.